Selective monoalkylation of hydroquinone in the presence of SO3H-functionalized ionic liquids as catalysts - Bhongale, Priyanka V.; Joshi, Sunil S.; Mali, Nilesh A. (Chemical Papers, 2020)
A process aiming atO-alkylation of hydroquinone (HQ), where ionic liquids (ILs) act as catalyst is objectively described. Five SO3H-functionalized ILs having different cations were prepared and characterized by NMR and FTIR techniques. The acidity and thermal stability of ILs were determined by Hammett function and thermogravimetric analysis (TGA), respectively. The catalytic activity of these ILs were tested forO-alkylation of HQ with methanol in 4-methoxyphenol (4MP) in the presence of small amount of benzoquinone (BQ). The effect of reaction parameters such as temperature, time, catalyst loading and substrate concentration on the conversion of HQ and product distribution was examined and optimized to maximize the yield of 4MP using 1,3-disulfonic acid imidazolium hydrogen sulfate (IL2) catalyst. Maximum yield of desired product 4MP 93.79% was obtained at 338 K temperature, 5.45 x 10(-2) mol HQ, 8.33 x 10(-3) mol BQ, and 10.37 mol% catalyst loading in 120 min reaction time. Single-product formation was observed up to 338 K temperature but higher temperature (above 338 K) and longer reaction time resulted in the formation of 2,4-dimethoxyphenol (24DMP) as a by-product. Catalyst recyclability was also established up to the fifth run which showed no declination in its activity.
Keywords: 4-Methoxyphenol; Benzoquinone; Hydroquinone; ionic liquids; O-alkylation

Subcritical water hydrolysis of N-acetyl-D-glucosamine: hydrolysis mechanism, reaction pathways and optimization for selective production of 5-HMF and levulinic acid - Kulkarni, Sphurti Prakash; Dure, Shital N.; Joshi, Sunil S.; V. Pandare, Kiran; Mali, Nilesh A. (Carbohydrate Research, 2022)
In this study, the subcritical water hydrolysis of N-acetyl-D-glucosamine (NAG), a monomer of abundant renewable marine biopolymer chitin, for production of value-added chemicals is investigated. The enhanced ionization of water at subcritical conditions (200 degrees C; 50-100 bar), provides enough acidity for deacetylation of NAG resulting in 80% yield of acetic acid along with traces of formic acid, lactic acid, glucose, fructose, 5hydroxymethylfurfural (5-HMF),etc. The significant humin formation indicates that the self-condensation and polymerisation of 5-HMF is favored in water at subcritical conditions. A catalyst p-toluenesulfonic acid (p-TsOH) was employed to selectively convert NAG to levulinic acid (LA) via ring opening of 5-HMF previously formed during hydrolysis. The maximum yield of 27.13 +/- 1% and 53.46 +/- 1% of 5-HMF and LA, respectively, was obtained at process conditions optimized using Box-Behnken design coupled with response surface methodology. Subcritical water enables greener conversion of NAG to platform chemicals wherein the selective production can be achieved by tuning the process conditions.
Keywords: 5-Hydroxymethylfurfural; chitin; Glucosamine; levulinic acid; Response surface methodology; Subcritical water